Pasar Ikan Higienis berdasarkan Pola Aktivitas Pengguna, Studi Kasus Pasar Ikan di Bandar Lampung - Lastriana Simbolon; Yunita kesuma (LOSARI Jurnal Arsitektur, Kota dan Permukiman, 2022)
Indonesia is an archipelago with a remarkable potential for marine wealth. However, the magnitude of this potential is not well-balanced with the provision of good facilities and infratructure so as to improve the quality of fisheries in Indonesia, especially in Bandar Lampung. One way to improve the quality of fishery product is to provide the facilities and infrastructures of fisheries products in the form of a hygienic fish market (PIH) in accordance with the health requirements hygiene of food and environmental sanitation requirements which in Lampung, there is no hygienic fish market (PIH). The approach that can be used and applied is the activity scheme approach. The activity schemes studied in this research are the activities of main user, fisherman, traders and consumers. This approach of activity patters is considered to be able to provide an effective space layout in accordance with health requirements, hygiene of food and environmental sanitation requirements because it contains theories of relation between humans and the environment.